THE EFFECT OF SLEEP QUALITY ON MEMORY AND ITS REVIEW FROM ISLAMIC PERSPECTIVE - Nurhidayat, Ayu Alifa Nasucha; Nurhidayati, Ida Ratna (HEARTY, 2026)
The purpose of this study was to determine the effect of sleep quality on memory and its impact on Islamic perspectives. This study was an observational analytical study with a cross-sectional design, where observations of both variables were conducted only once at the same time. The sample was determined using a purposive sampling technique. The data collection instruments used were a questionnaire to assess sleep quality, the Pittsburgh Sleep Quality Questionnaire (PSQI), and direct tests to assess respondents' memory function using the CERAD and MoCA-Ina. The data were analyzed using univariate and bivariate analyses. The results showed: (1) The majority of respondents, 107 (88.4%), had poor sleep quality, and 14 (11.6%) had good sleep quality. (2) There was no significant relationship between sleep quality and memory function, with a p-value > 0.05. (3) According to Islamic perspective, implementing sleep patterns in accordance with the recommendations of the Prophet Muhammad (peace be upon him) is believed to improve sleep quality and thus enhance one's quality of life.